Acute lead poisoning in an indoor firing range - Štěpánek, Ladislav; Nakládalová, Marie; Klementa, Viktor; Ferenčíková, Veronika (Medycyna pracy, 2020)
The presented case demonstrates that acute lead poisoning may occur due to just short-term exposure to a mixture of lead-containing dust and ammunition. Such exposure may result in high blood lead levels persisting for years in the absence of any symptoms. A middle-aged male with a history of an approximately 7-day cleanup of an old recreational firing range with large ammunition and dust deposits presented to an emergency department with abdominal pain, dyspnea, fatigue and impaired cognitive function. Given his occupational history, specific tests were performed that showed high lead concentrations in both blood and urine. The patient was diagnosed with acute lead poisoning. He was started on chelation therapy that improved both clinical and laboratory parameters. Over a subsequent nearly 3-year follow-up, the patient's blood lead levels fluctuated and continued to be increased. Given the absence of other sources of lead exposure, these were likely due to the formation of bone deposits. Med Pr. 2020;71(3):375-9.
Keywords: Firearms; Abdominal Pain; Occupational Exposure; pracoviště; chelation therapy; lead poisoning; Humans; lidé středního věku; Workplace; Polsko; bolesti břicha; výsledek terapie; lidé; Poland; střelné zbraně; znečištění vzduchu ve vnitřním prostředí; anemia; Male; occupational exposure to lead; Middle Aged; pracovní expozice; Lead Poisoning; Treatment Outcome; Air Pollution, Indoor; chelátory; urine lead level; blood lead level; mužské pohlaví; Acute Disease; Chelating Agents; akutní nemoc; otrava olovem